Investigating the Impact of Using an Alternate Classification Method for Race and Hispanic Ethnicity on Rates of Reported Gonorrhea. Issue 11 (November 2020) - Picchetti, Viani; Chesson, Harrell; Braxton, Jimmy; Torrone, Elizabeth
Abstract : Background: We aimed to examine how the classification of gonorrhea cases by race and Hispanic ethnicity (HE) affects the measurement of racial/HE disparities in the rates of reported gonorrhea. Methods: We examined gonorrhea cases reported through the National Notifiable Diseases Surveillance System from January 1, 2010, to December 31, 2017, and assigned race and HE using (1) "current classification, " where cases with HE are classified as Hispanic regardless of race (e.g., Hispanic, non-Hispanic White, and non-Hispanic Black), and 2) "alternate classification, " which separates each race category by HE (e.g., Hispanic White and non-Hispanic White). We estimated annual gonorrhea rates during 2010 to 2017 by race/HE category and calculated disparity measures (index of disparity, population-attributable proportion, and Gini coefficient) for gonorrhea rates under each classification strategy. Results: All disparity measures revealed decreases in racial/HE disparities in the rates of reported gonorrhea during 2010 to 2017, regardless of classification strategy; however, the magnitude of the disparity and the percent change in the disparity over time varied across disparity measures. Conclusions: Understanding how classification of race/HE affects observed disparities is critical when monitoring interventions to reduce disparities and improve health equity. Abstract : Racial/Hispanic ethnicity disparities in the rates of reported gonorrhea decreased in 2010 to 2017; however, the magnitude of the disparity varied depending on how race/Hispanic ethnicity was classified.Supplemental digital content is available in the text.